Identification of a putative estrogen response element in the gene encoding brain-derived neurotrophic factor. - Sohrabji, F (1995)
We have been studying the role and mechanism of estrogen action in the survival and differentiation of neurons in the basal forebrain and its targets in the cerebral cortex, hippocampus, and olfactory bulb. Previous work has shown that estrogen-target neurons in these regions widely coexpress the mRNAs for the neurotrophin ligands and their receptors, suggesting a potential substrate for estrogen-neurotrophin interactions. Subsequent work indicated that estrogen regulates the expression of two neurotrophin receptor mRNAs in prototypic peripheral neural targets of nerve growth factor. We report herein that the gene encoding the neurotophin brain-derived neurotrophic factor (BDNF) contains a sequence similar to the canonical estrogen response element found in estrogen-target genes. Gel shift and DNA footprinting assays indicate that estrogen receptor-ligand complexes bind to this sequence in the BDNF gene. In vivo, BDNF mRNA was rapidly up-regulated in the cerebral cortex and the olfactory bulb of ovariectomized animals exposed to estrogen. These data suggest that estrogen may regulate BDNF transcription, supporting our hypothesis that estrogen may be in a position to influence neurotrophin-mediated cell functioning, by increasing the availability of specific neurotrophins in forebrain neurons.